1997
DOI: 10.1111/j.1365-2044.1997.az0083b.x
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the pre‐operative assessment of patients for elective repair of abdominal aortic aneurysm

Abstract: SummarySevoflurane, desflurane and isoflurane were compared using a circle system in 97 patients undergoing short surgical procedures. Using initial high flows, the time intervals to equilibration between inspired and end-expired agent concentrations were measured; equilibration was defined as F E = F I 0:8. The mean (SD) times obtained for sevoflurane, desflurane and isoflurane were 8.2 (2.1) min, 3.8 (0.7) min and 19.7 (6.5) min, respectively. These times were significantly different from each other (p < 0:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…3 A survey-based study demonstrated considerable variations in the pre-operative assessment of such patients. 4 It has been argued that simple measurement of ejection fraction is of no value in the risk stratification of patients with aneurysms suitable for open repair.…”
Section: Discussionmentioning
confidence: 99%
“…3 A survey-based study demonstrated considerable variations in the pre-operative assessment of such patients. 4 It has been argued that simple measurement of ejection fraction is of no value in the risk stratification of patients with aneurysms suitable for open repair.…”
Section: Discussionmentioning
confidence: 99%
“…a = echocardiogram; b = cardiac stress test; c = arterial blood gases; d = pulmonary function tests. 4 showed by postal survey of 100 United Kingdom hospitals that there was a marked disparity in preoperative investigation of patients before elective abdominal aortic aneurysm repair. Our survey suggests that overinvestigation and tmder-investigation (using the attending anaesthetist as the gold standard) of patients seen in the PACC by one anaesthetist, and on the day of surgery by another, is likely to be a frequent problem.…”
Section: Discussionmentioning
confidence: 99%
“…Although conclusions must be limited by the response rate of 64%, this rapid availability and access to cardiologists and cardiological investigations is unusual by UK standards. The wide awareness of the literature but enormous variations in practice is very similar to that of Canadian and UK anaesthetists [41,42] and may reflect the lack of conclusive evidence for betablockade in intermediate or low risk patients undergoing major surgery [43] as recognised by the ACC guidelines [2]. This question is now being addressed by ongoing multicentre studies, including the POISE study, which aims to recruit 10 000 patients worldwide.…”
Section: The Role Of Beta-blockadementioning
confidence: 99%